Helical electronic transitions of spiroconjugated molecules. Issue 52 (4th June 2021) - Garner, Marc H.; Corminboeuf, Clemence
Abstract : The π–π* transitions of disubstituted spiropentadiene become helical due to mixing of its two perpendicular π-systems. The helicity is symmetry-protected and gives rise to experimentally observable effects, such as optical activity. Abstract : The two π-systems of allene can combine into helical molecular orbitals (MOs), yet the helicity is lost in the π–π* transitions due to excited state mixing. In spiroconjugated molecules the relative orientation of the two π-systems is different and consequently only half the π-MOs become helical. We show that the helicity of the electronic transitions of methyl-substituted spiropentadiene is symmetry protected. As a result, helical π-conjugation can manifest in observable electronic and chiroptical properties.